Microstructure and mechanical properties of a forged β-solidifying γ TiAl alloy in different heat treatment conditions. (March 2015) - Bolz, S.; Oehring, M.; Lindemann, J.; Pyczak, F.; Paul, J.; Stark, A.; Lippmann, T.; Schrüfer, S.; Roth-Fagaraseanu, D.; Schreyer, A.; Weiß, S.
Abstract: In the cast condition γ titanium aluminide alloys that solidify completely through the β phase are characterized by fine and homogeneous microstructures, weak textures and low segregation. For these reasons such alloys have a relatively good workability and can be closed-die forged without preceding ingot breakdown even if the alloys contain no large fractions of the β phase at the working temperature. The present work was devoted to a combined study of the constitution and microstructural morphologies that develop in various two-step heat treatments of a single-step forged β solidifying alloy. The study included high-energy X-ray diffraction for in situ investigations of the constitution at the heat treatment temperature. It was observed that the phase transformations are quite sluggish in the material which results in fine microstructures and some conditions that significantly deviate from thermodynamic equilibrium. Further, tensile and creep testing was carried out on the different material conditions in order to identify the range in which the properties can be varied. It is found that this easily forgeable material exhibits comparable strength, ductility and creep strength as more conventional peritectically solidifying alloys. Highlights: The phase transformations in the alloy are sluggish and result in fine microstructures. The cooling rate and annealing temperature have a dominant influence on the properties. The mechanical properties compare well with those of advanced peritectic TiAl alloys.